Post-mortem histopathology underlying β-amyloid PET imaging following flutemetamol F 18 injection - Ikonomovic, Milos D.; Buckley, Chris J.; Heurling, Kerstin; Sherwin, Paul; Jones, Paul A.; Zanette, Michelle; Mathis, Chester A.; Klunk, William E.; Chakrabarty, Aruna; Ironside, James; Ismail, Azzam; Smith, Colin; et al. (Acta neuropathologica communications, 2016)
In vivo imaging of fibrillar β-amyloid deposits may assist clinical diagnosis of Alzheimer's disease (AD), aid treatment selection for patients, assist clinical trials of therapeutic drugs through subject selection, and be used as an outcome measure. A recent phase III trial of [ F]flutemetamol positron emission tomography (PET) imaging in 106 end-of-life subjects demonstrated the ability to identify fibrillar β-amyloid by comparing in vivo PET to post-mortem histopathology. Post-mortem analyses demonstrated a broad and continuous spectrum of β-amyloid pathology in AD and other dementing and non-dementing disease groups. The GE067-026 trial demonstrated 91% sensitivity and 90% specificity of [ F]flutemetamol PET by majority read for the presence of moderate or frequent plaques. The probability of an abnormal [ F]flutemetamol scan increased with neocortical plaque density and AD diagnosis. All dementia cases with non-AD neurodegenerative diseases and those without histopathological features of β-amyloid deposits were [ F]flutemetamol negative. Majority PET assessments accurately reflected the amyloid plaque burden in 90% of cases. However, ten cases demonstrated a mismatch between PET image interpretations and post-mortem findings. Although tracer retention was best associated with amyloid in neuritic plaques, amyloid in diffuse plaques and cerebral amyloid angiopathy best explain three [ F]flutemetamol positive cases with mismatched (sparse) neuritic plaque burden. Advanced cortical atrophy was associated with the seven false negative [ F]flutemetamol images. The interpretation of images from pathologically equivocal cases was associated with low reader confidence and inter-reader agreement. Our results support that amyloid in neuritic plaque burden is the primary form of β-amyloid pathology detectable with [ F]flutemetamol PET imaging. ClinicalTrials.gov NCT01165554. Registered June 21, 2010; NCT02090855. Registered March 11, 2014.